Associations of the density and proximity of the outlets of tobacco and other nicotine-containing products with increased levels of depression, anxiety and stress among the population of 3 Russian regions - M. G. Gambaryan; A. V. Kontsevaya; A. A. Antsiferova; D. K. Mukaneeva; V. A. Kutsenko; N. A. Pustelenin; M. B. Khudyakov; A. V. Kudryavtsev; E. M. Filichkina; S. V. Glukhovskaya; A. V. Solovyova; S. A. Shalnova; et al. (Кардиоваскулярная терапия и профилактика, 2023)
Aim. To study the relationship of the density and proximity of tobacco products (TPs) and electronic nicotine delivery systems (ENDS) with increased levels of depression, anxiety and stress among the population in 3 constituent entities of the Russian Federation.Material and methods. The work used data from the Epidemiology of Cardiovascular Diseases and their Risk Factors in Regions of Russian Federation-3 (ESSE-RF3) study in 3 Russian regions (Arkhangelsk, Sverdlovsk and Tver regions) among the population aged 35-64 years (n=1674), who signed a consent to participate in the study. We analyzed data on the status of smoking and consumption of ENDS, passive smoking, attempts to quit smoking, as well as the presence of depression, anxiety (Hospital Anxiety and Depression Scale (HADS) score ≥8) and stress (Perceived Stress Scale (PSS) >21). Elements of urban infrastructure (data collection: January-March 2022) selling TPs and ENDS were assessed using aт OpenStreetMap-based program. Associations were established using logistic regression analysis.Results. With a twofold increase in the distance of TP and ENDS outlets from the place of residence, the depression probability was reduced by 13% (odds ratio (OR) 0,87; 95% confidence interval (CI): 0,79-0,96) and by 12% (OR 0,88; 95% CI: 0,78-0,99), respectively. With increase in distance from of TP outlets, the anxiety decreased probability by 12% (OR 0,88; 95% CI: 0,81-0,97). With an increase in the number of TP outlets within a radius of 1000 m from the place of residence, there were an increase in the probability of depression (OR 1,18; 95% CI: 1,031,36), anxiety (OR 1,12; 95% CI: 1-1,26) and stress (OR 1,24; 95% CI: 1,05-1,46). A greater number of ENDS outlets within a radius of 1000 m and 400 m was associated with a high likelihood of depression (OR 1,17; 95% CI: 1,02-1,34 and OR 1,25; 95% CI: 1,04-1,47, respectively). An increased depression probability was found in those exposed to tobacco smoke at home (OR 1,88; 95% CI: 1,27-2,73) and at work (OR 1,67; 95% CI: 1,14-2,41). An increase in the number of attempts to quit smoking doubles the odds of depression (OR 2,40; 95% CI: 1,35-4,23) and anxiety (OR 2,00; 95% CI: 1,18-3,38).Conclusion. Unfavorable environmental factors, including the proximity and density of TP and ENDS outlets, can increase the probability of depression, anxiety and stress among the population living in these areas.